Application of Sanctions for Inmates Who Violate Order in Class I Correctional Institution Surabaya - Pratama, Rendi Arif; Rizky, Muchammad Catur; Samuji, Samuji (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The implementation of sanctions against inmates who violate the provisions of the code of conduct based on Law Number 20 of 2022 concerning Correctional Services and Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 8 of 2024 concerning the Implementation of Security and Order in Correctional Work Units. It is closely related to the Coaching of Prisoners in the Class I Correctional Institution of Surabaya. This study aims the application of sanctions for correctional inmates who violate discipline in Class I Correctional Institution Surabaya. In this study, the method used is qualitative. The results of the study show that the application of sanctions for inmates who violate the provisions of the code of conduct is in the form of minor violations, moderate violations, and severe violations. The imposition of sanctions is applied to all Correctional Assisted Citizens in the Prison to improve and educate Correctional Assisted Citizens who violate the provisions of the Correctional Institution. The imposition of sanctions is carried out in a structured manner and based on applicable rules. Still, there are sanctions given by the conditions in the field for the effectiveness of the sanctions to cause a deterrent effect on violators. Factors that affect the process of imposing sanctions include the level of violations, the attitude and behavior of the inmates, and the factors of the Correctional Institution itself. This research is expected to provide input for related parties in increasing the effectiveness of the discipline enforcement system in Correctional Institutions.